Caracterização do cuidador familiar em relação ao conhecimento sobre hidrocefalia - Oliveira, Débora Moura da Paixão (2009)
Hydrocephalus is a disease frequently mentioned in literature, but, the caregivers‟ knowledge about the disease is not well assessed. To characterize the caregivers of hydrocephalus patients; identify the fonts of formation to assume activities how to care; to verify caregivers‟ knowledge about hydrocephalus; to relate the caregiver‟ knowledge and level of child complications. Descriptive, exploratory and quantitative study, using a standardized interview technique. The survey was performed with caregivers at Aracaju University Hospital between November 2007 and August 2008. Fifty-four caregivers answered the interview. The mean age was 27.3 ± 7 years, with absolute predominance of females. There was a positive correlation on the number that they had left to work to be caregivers. Twenty-five caregivers (46.3%) received information about how to care and 53.7% learned to take care by themselves. The education level of the caregiver had a significant effect on the knowledge about definition, causes, complications, surgery and the shunt objectives. The knowledge about complications and surgery was significantly bigger in caregivers of children with sequels (P=0.003). The caregivers received little professional information. The education level of the caregiver had a positive correlation to on increased knowledge. Caregivers of children with sequels were related to on increased knowledge about important aspects on hydrocephalus.